ANALISIS UKURAN PORI BIOKOMPOSIT [SERICIN-BIOPLASTIK] PADA BERBAGAI PEMBEKUAN DENGAN METODE TAGUCHI - Putra, Gaustama (Jurnal Optimalisasi, 2017)
Increased demand for medical materials, triggering research into alternativemedical materials. Alternative materials should have the same characteristics for the patient's body. Sericin is a protein that has biocompatible, biodegradable and other important properties. Sericin is widely used in biomedical applications, it is thought that sericin is a promising natural resource as an alternative medical material. This study analyzed pore diameter in sericin-bioplastic biocomposites by Taguchi method. Bioplastics of 3 variations of tapioca starch were 16 g, 14 g, and 10 g, mixed 80 ml of aquades and 6 ml of glycerin. Sericin was determined 0.03%, 0.1%, and 0.3% by weight of tapioca starch. The biocomposite undergoes freeze drying process and is frozen at -25oC, -45oC, and -80oC for one day. SEM test to see pore diameter and biocomposite structure. Optimal analysis was performed for optimal combinations of sericin-bioplastic biocomposites. The SEM results showed pore diameters qualified for regeneration of skin tissue on freezers C -C, F, and I -25oC biocomposites of 41.94 Î¼m, 33.416 Î¼m and 32.743 Î¼m respectively. Calculation of average response and maximum SNR at 16 g tapioca starch, 0.03% sericin and -25oC temperature. The predicted and confidence interval values for averages are large from 11,656 Î¼m and small from 54,602 Î¼m, SNR is large from 31,940 Î¼m and small from 33,642 Î¼m. The optimal experimental conditions for confirmation of large pore diameter for averages were large from 32.342 Î¼m and small from 34.206 Î¼m, large SNR of 32.342 Î¼m and small from 34.206 Î¼m.Keywords: Composition optimization, alternative medical materials, sericin- bioplastic biocomposites, Taguchi Methods, SEM